Processed meat consumption increases risk of type 2 diabetes mellitus in adults aged 40 years and older (Universa Medicina, 2022)
Background Type 2 diabetes mellitus (T2DM) remains a public health problem in the world, including Indonesia. The high mortality of T2DM is triggered by an unhealthy eating pattern and sedentary lifestyle. We aimed to investigate the relationship of food intake pattern and its related factors with T2DM in adults 40 years and older.MethodsThis was a cross-sectional study conducted on 11,022 men and women with T2DM aged 40 years and older. Major dietary patterns were collected and multiple logistic regression analysis was used to determine the effect of covariates. Statistical significance was set at a p-value of 40 years comprised 50.17% and 26.19%, respectively, of the 11,022 respondents. Individuals aged over 50 years had a higher risk of developing diabetes than those aged less than 50 years (AOR =5.67, 95% CI=1.37-21.94, p